Steganography Software for Hiding Message in Digital Image by using Five Modulus Method - Nichander Chiunata; Octara Pribadi; Feriani Astuti Tarigan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Steganography is a technique for concealing information within digital media to prevent unauthorized detection. This research presents the design of a text hiding system using the Five Modulus Method (FMM) applied to digital images. The method utilizes modulus 5 operations on pixel values to embed secret messages discreetly while preserving the visual quality of the image. The developed system includes features for embedding, extracting, and comparing images to evaluate the results. The test results show that the FMM method successfully embeds text messages with minimal changes to the original image, demonstrated by PSNR values exceeding 40 dB in most tests. The extraction process also accurately retrieves the hidden messages as long as the image remains unaltered. However, this method has limitations in data capacity and is vulnerable to lossy compression. This study concludes that the FMM method is effective for hiding small to medium-sized messages and is suitable for lightweight secure communication applications.